1990
DOI: 10.1111/j.1471-4159.1990.tb05787.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Opioid Receptor Binding by Cis and Trans Fatty Acids

Abstract: In synaptosomal brain membranes, the addition of oleic acid (cis), elaidic acid (trans), and the cis and trans isomers of vaccenic acid, at a concentration of 0.87 mumol of lipid/mg of protein, strongly reduced the Bmax and, to a lesser degree, the binding affinity of the mu-selective opioid [3H]Tyr-D-Ala-Gly-(Me)Phe-Gly-ol ([3H]DAMGO). At comparable membrane content, the cis isomers of the fatty acids were more potent than their trans counterparts in inhibiting ligand binding and in decreasing membrane microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…In agreement with lacking regulation by GTP (4) have shown that the biphasic binding of this antagonist reflects interactions with both u (high-affinity component) and 6 (low-affinity component) opioid receptors (33). These interpretations are in line with the limited binding selectivity of NTX in brain (33,34).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In agreement with lacking regulation by GTP (4) have shown that the biphasic binding of this antagonist reflects interactions with both u (high-affinity component) and 6 (low-affinity component) opioid receptors (33). These interpretations are in line with the limited binding selectivity of NTX in brain (33,34).…”
Section: Resultssupporting
confidence: 68%
“…3) and opioid-sensitive GTPase activity. (29) and receptor coupling to low Km GTPase (30). Earlier it was shown that, after inactivation of opioid-sensitive adenylate cyclase in NG108-15 cells by N-ethylmaleimide, enzyme activity was restored by fusion of the hybrid cells and C6 glioma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the molecular mechanisms elevating ENK and DYN transcripts in response to fat remain to be characterized, evidence demonstrates a direct stimulatory effect of short-chain fatty acids on ENK gene expression in PC12 rat cells via an intact PKA signaling pathway, with a possible involvement of lipid-activated transcription factors [52]. Fatty acids may also modulate the binding of opioid peptides to their receptor [53]. This evidence indicates that opioids in the PVN, as shown for GAL, are responsive to circulating lipids, TG or fatty acids, which may mediate the stimulatory effect of dietary fat on these peptides.…”
Section: Relation Of Opioid Peptides To Dietary Fatmentioning
confidence: 99%
“…Although the molecular mechanisms elevating ENK and DYN transcripts within 15 and 60 min remain to be characterized, evidence (44) demonstrates a direct stimulatory effect of short-chain fatty acids on ENK gene expression in PC12 rat cells via an intact PKA signaling pathway, with a possible involvement of lipid-activated transcription factors. It is of interest that, in addition to their effects on peptide expression, fatty acids may also modulate the binding of opioid peptides to their receptor (58).…”
Section: Stimulatory Effect Of Dietary Fat On Opioid Peptides In the mentioning
confidence: 99%